Analysis of Arabic Language Textbooks for Nahwu and Sharaf in Madrasah Aliyah Religious Specialization Class XI - Srirehani, Melinda Dewi; Yansah, Wahyu Febri; Muhaiban, Muhaiban (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study analyzes the Arabic Language (Nahwu & Sharaf) textbook for Class XI of the Madrasah Aliyah religious specialization program. Using a qualitative descriptive method, data were collected through document analysis and evaluated against curriculum standards. Findings reveal that the textbook is systematically structured with interrelated chapters, supporting continuous learning. Strengths include an inductive approach, relevance to the curriculum, and integration of socio-cultural values. However, weaknesses such as inconsistent use of harakat, limited illustrative visuals, and less varied material delivery hinder its effectiveness. The study concludes that while the textbook is effective, improvements in presentation, material consistency, and adaptability to diverse student characteristics are needed to enhance motivation and learning outcomes.